Analysis of Community Based Tourism (CBT) Standards as the Basis for Development in Ketenger Tourism Village, Banyumas Regency - Arief Bakhtiar Darmawan; Soni Martin Anwar (Program Pascasarjana, 2021)
This study aims to identify community participation in developing a tourist village and implement tourism development in Ketenger Village through community-based tourism (CBT). Ketenger Village is a tourist village having various destinations and tourist areas so that the potential for village development can still be developed. The data in this study were collected through field observations, interviews, and focus group discussions with related parties. Data were analyzed using qualitative methods. The study results indicated that the participation or involvement of the Ketenger Village community in several CBT standards had been partly met, while others need to be improved. Despite having Pokdarwis (Tourism-aware Group), the village government was still the main motor of tourism. Therefore, some of the main development opportunities for Ketenger Village that can be done are improving the quality of community management (in planning, implementation, and evaluation), improving the quality of human resources, encouraging host and tourist interaction, and maximizing marketing through social media (not only depending on newspaper journalists).Keywords: community-based tourism, community participation, Ketenger Village, tourism.